2016
DOI: 10.1002/nau.23084
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lower urinary tract symptoms in patients with idiopathic normal pressure hydrocephalus

Abstract: Patients with iNPH present with mild-moderate incontinence of which nocturia is the most common symptom, urge incontinence the most bothersome, with 100% of patients having detrusor overactivity. Younger patients experienced greater bother related to LUTS. To our knowledge, this is the only prospective evaluation of urinary symptoms in patients with new-onset iNPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…Urodynamics testing demonstrated that 100% of iNPH patients had detrusor overactivity. 5 This was in line with findings from prior smaller retrospective studies. 3,8 The mainstay of treatment for iNPH is with ventriculoperitoneal (VP) shunting.…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…Urodynamics testing demonstrated that 100% of iNPH patients had detrusor overactivity. 5 This was in line with findings from prior smaller retrospective studies. 3,8 The mainstay of treatment for iNPH is with ventriculoperitoneal (VP) shunting.…”
Section: Introductionsupporting
confidence: 90%
“…Responses to validated questionnaires at the initial patient visit were reported previously. 5 All patients with a diagnosis of iNPH underwent provocative testing with lumbar puncture, measurement of opening pressure, and removal of a standard volume of spinal fluid per institution protocol. Patients were observed following this procedure for clinical improvement in iNPH symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations